A Model for the Genetic Employment of Chickens Local to Warm Climate 1. Crossing with a Fast Growing Strain and Growth Patterns of the Crossbreds - El-Gendy, Essam A. (International Journal of Poultry Science, 2009)
A breeding program aims to develop a chicken population inherent for heat tolerance and fast growth was started using a naked-neck local breed in Egypt that performs heat tolerance. The local breed was crossed with the sire line of a normally feathered commercial broiler strain. The crossbreds were raised in a heating treatment (35oC from hatch to 6 weeks, then reduced to 24oC) or a non-heating treatment (35oC from hatch to 3 days, and reduced gradually to reach 24°C). Body weights of the crossbreds, across ages, were significantly around twofold heavier than those of the locals. The crossbreds weighed 641.8 g at 6 weeks of age versus 303.0 g for the locals. The 2-4 week growth rate was 73.7% for the crossbreds versus 60.2% for the locals. The Na/na crossbreds were significantly heavier than na/na crossbreds when heated, and the differences were not significant when non-heated. The spread of 6-week body weights of the crossbreds was remarkably different from that of the locals and the difference was mainly attributed to the variation brought in through the flow of genes. The heterotic effects on body weights were significant in both heated and non-heated crossbreds and expressed a large source of non-additive genetic variation. Heterosis estimates in body weights and growth rates were age and environment specific, and were significantly higher for the heated than for non-heated crossbreds, indicating the flow of genes influence growth and heat tolerance. The results demonstrate remarkable changes in the frequencies of non-allelic genes that influence growth and propose the genetic selection for increased 6-week body weight in the naked-neck and normally feathered crossbreds.